50 YEARS OF NEWBORN SCREENING FOR CONGENITAL HYPOTHYROIDISM: EVOLUTION OF INSIGHTS IN ETIOLOGY, DIAGNOSIS AND MANAGEMENT: Management during pregnancy and long-term outcomes of adult patients with congenital hypothyroidism - Charles Mégier; Dominique Luton; Athanasia Stoupa (European Thyroid Journal, 2025)
Congenital hypothyroidism (CH) is a lifelong condition, diagnosed shortly after birth through newborn screening in one-third of countries worldwide. When diagnosed and treated early in nonsyndromic CH, most patients exhibit similar fertility, metabolic and cardiovascular health, bone health, and quality of life compared to unaffected individuals. Special precautions are required for adult female patients with CH during pregnancy to ensure optimal management and to prevent serious maternal and fetal complications. In this review, we summarize the current knowledge on comorbidities and the long-term management of adults with CH, with a particular focus on pregnancy.